Adjusting the Ideal Islamic Religious Education Curriculum to the Development of AI-Based Technology - Sari Hernawati; Muhammad Hafizh; Muhammad Nurfaizi Arya Rahardja (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2024)
The development of technology is currently experiencing a very rapid development, one of which is the emergence of an innovation called AI (artificial intelligence). Islamic religious education indirectly gets an impact on the emergence of AI (artificial intelligence) so that it requires adjustments in the Islamic religious education curriculum so that the Islamic religious education curriculum remains ideal with the times. This research is a qualitative research using library study research method with causal descriptiva analysis. Primary sources in this research are all literature relevant to this theme, namely the Islamic religious education curriculum and AI (artificial intelligence) and secondary sources focus on other literature that is indirectly relevant to this research. The result of this study is to describe five adjustments to the Islamic religious education curriculum towards AI (artificial intelligence), namely understanding the concept of technology and AI, ethics of using AI, digital literacy skills, character education, and strengthening Islamic values.